Extended endoscopic transplanum–transtuberculum approach for pituitary adenomas. (June 2013) - Barazi, S. A.; Pasquini, E.; D'Urso, Pietro I.; Zoli, M.; Mazzatenta, D.; Sciarretta, V.; Frank, G.
Abstract Few pituitary adenomas require removal through a transcranial route. This may be associated with more significant morbidity and mortality, compared to the transsphenoidal approach. An endoscopic, extended, transplanum–transtuberculum approach (ETTA) in selected pituitary adenomas may offer an alternative to the transcranial route. We describe our technique and experience of ETTA in pituitary adenomas over 10 years. Between 2000 and 2010, we performed 700 endoscopic endonasal procedures for pituitary adenomas. Nineteen patients (13 men; mean age, 48 years; range, 22–76 years) underwent 22 ETTAs. Thirteen patients had non-functioning adenomas. Three tumor groups were identified: (1) tumors developing in or around the pituitary stalk; (2) tumours with sub- frontal extension and (3) tumours with a major extrasellar component. Mean follow-up was 37 months (range 6–72 months). Gross total resection was achieved in 11 procedures (no recurrences), with partial tumour resection in 11 procedures. Of the 12 patients with visual symptoms, ten improved. Of eight patients with hormonal hypersecretion four were cured. Complications included CSF leak (14%), haemorrhage (9%), hemiplegia (5%). There were no mortalities. Experience using the ETTA for pituitary adenomas is limited because it is indicated in highly selected cases (3.1% of our series). An absolute indication is represented by ectopic secreting pituitary stalk/peri-stalk adenomas. ETTA is a useful option in midline frontal adenomas and adenomas with a major extrasellar component, but has a higher morbidity than that seen in the standard transsphenoidal approach. A study comparing ETTA versus transcranial resection is highly desirable.